Analysis of stem cell collections in adult patients with Ewing sarcoma. Issue 8 (8th July 2022) - Franke, Georg‐Nikolaus; Pfannes, Roald; Heyn, Simone; Brückner, Mandy; Rieprecht, Susanne; Bach, Enrica; Remane, Yvonne; Leiblein, Sabine; Pönisch, Wolfram; Niederwieser, Dietger; Schwind, Sebastian; Platzbecker, Uwe; et al.
Abstract: Background: Ewing sarcoma is one of the most frequent soft‐tissue tumors in pediatric patients. The current treatment protocols recommend stem cell apheresis (SCA) after completion of the second course of induction therapy with vincristine, ifosfamide, doxorubicine, and etoposide (VIDE). The feasibility of SCA and graft compositions in adult patients with Ewing sarcoma have not been previously analyzed. Methods and Materials: The authors analyzed 29 stem cell collections of 19 adult patients (9 male, 10 female) at a median age of 27 (range 19–53) years mobilized after VIDE ( n = 17), cyclophosphamide/topotecan ( n = 1) or vincristine, dactinomycin and ifosfamide ( n = 1) chemotherapy. All patients were mobilized with filgrastim 5 μg/kg twice daily from day +7 of chemotherapy. The collections were performed if CD34+ cell count in peripheral blood was >10/μL. The target yields were ≥4×10 6 CD34+ cells/kg body weight. Results: Median CD34+ cells/μL in peripheral blood before SCA were 45.8 (range 6.7–614.4)/μL. The median cumulative yields were 10.6 (range 1.5–38.8) CD34+ cells/kg body weight and ≥2×10 6 in all but two patients (89%). CD34, CD3, and CD56 yields in collections after the third VIDE and after later courses did not differ. Four patients underwent high‐dose therapy with autologous transplantation, and all were engrafted. Discussion: Stem cell mobilization is feasible in most Ewing sarcoma patients. Additionally, the present study's data suggest that it is safe to postpone stem cell collection to a later VIDE chemotherapy cycle if medically indicated.